A highly efficient and safe gene delivery platform based on polyelectrolyte core–shell nanoparticles for hard-to-transfect clinically relevant cell types. Issue 41 (2nd October 2020) - Tarakanchikova, Yana; Muslimov, Albert; Sergeev, Igor; Lepik, Kirill; Yolshin, Nikita; Goncharenko, Alexander; Vasilyev, Kirill; Eliseev, Igor; Bukatin, Anton; Sergeev, Vladislav; Pavlov, Sergey; Popov, Alexey; et al.
Abstract : The polyelectrolyte nanocarriers' based on nanosized vaterite particles as a novel tool for genetic material delivery into the clinically relevant cell types and potential application of described technology in gene therapy approaches. Abstract : While DNA and messenger RNA (mRNA) based therapies are currently changing the biomedical field, the delivery of genetic materials remains the key problem preventing the wide introduction of these methods into clinical practice. Therefore, the creation of new methods for intracellular gene delivery, particularly to hard-to-transfect, clinically relevant cell populations is a pressing issue. Here, we report on the design of a novel approach to format 50–150 nm calcium carbonate particles in the vaterite state and using them as a template for polymeric core–shell nanoparticles. We apply such core–shell nanoparticles as safe and efficient carriers for mRNA and pDNA. We prove that such nanocarriers are actively internalized by up to 99% of primary T-lymphocytes and exert minimal toxicity with the viability of >90%. We demonstrate that these nanocarriers mediate more efficient transfection compared with the standard electroporation method (90% vs. 51% for mRNA and 62% vs. 39% for plasmid DNA) in primary human T-lymphocytes as a model of the hard to transfect type that is widely used in gene and cell therapy approaches. Importantly, these polymeric nanocarriers can be used in serum containing basic culture medium without special conditions and equipment, thus having potential for being introduced in clinical development. As a result, we have provided proof-of-principle that our nanosized containers represent a promising universal non-viral platform for efficient and safe gene delivery.